1996
DOI: 10.1007/bf00138864
|View full text |Cite
|
Sign up to set email alerts
|

Property and contract rights in autocracies and democracies

Abstract: We present and test empirically a new theory of property and contract rights. Any incentive an autocrat has to respect such rights comes from his interest in future tax collections and national income and increases with his planning horizon. We find a compelling empirical relationship between property and contract rights and an autocrat's time in power. In lasting --but not in new --democracies, the same rule of law and individual rights that ensure continued free elections entail extensive property and contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
317
3
9

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(340 citation statements)
references
References 20 publications
11
317
3
9
Order By: Relevance
“…The ICRG indicators are standard in the literature for measuring institutional progress (see Djankov et al 2006 or Akitoby andStratmann 2010), as they capture the legal and political environment governing both property rights and the political system. As a check on the subject investor protection ranking, I also utilize an objective indicator for property rights, contract-intensive money, which represents the proportion of money held inside the formal banking sector (see Clague et al 1996 andHartwell 2013). In contrast to the investor protection indicator, contract-intensive money is more accurately described as realized property rights, as it measures the behavior of individuals in reaction to perceived changes in property rights.…”
Section: The Data and Empirical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The ICRG indicators are standard in the literature for measuring institutional progress (see Djankov et al 2006 or Akitoby andStratmann 2010), as they capture the legal and political environment governing both property rights and the political system. As a check on the subject investor protection ranking, I also utilize an objective indicator for property rights, contract-intensive money, which represents the proportion of money held inside the formal banking sector (see Clague et al 1996 andHartwell 2013). In contrast to the investor protection indicator, contract-intensive money is more accurately described as realized property rights, as it measures the behavior of individuals in reaction to perceived changes in property rights.…”
Section: The Data and Empirical Modelmentioning
confidence: 99%
“…In the first instance, as we are attempting to ascertain the profitability of particular banks, as influenced by institutions, contract-intensive money is a suitable proxy as no one bank influences the indicator; that is, while it functions as a vote of confidence in the entire banking sector and property rights in general, unless you are a country like Turkmenistan with a monobank structure, no single bank can dominate the outcome of the indicator. Moreover, while contract-intensive money may sometimes be thought of as a proxy for financial depth (Williams and Siddique 2008), previous empirical tests by Clague et al (1996) have shown that contract-intensive money does indeed capture different effects than broader financial sector development. This is indeed the case here for, as Table 4 shows, while there is some moderate correlation between CIM and other financial depth variables (with the strongest being with country-wide bank capital to assets ratio at 0.5094), the extent of the correlations do not suggest that contract-intensive money cannot be used.…”
Section: The Data and Empirical Modelmentioning
confidence: 99%
“…If our theory is correct, we should not see a consistent positive effect on foreign aid. This robustness test is particularly important because many political economists have found that young and fragile democracies are not as reliable as established democracies (Clague et al 1996;Keefer 2007;Przeworski 1991).…”
Section: Democracy or Democratization?mentioning
confidence: 99%
“…We make use of Jaggers and Gurr's measure of democracy (1995), which came from the Polity III database. Numerous studies have considered the effect of political (in)stability and property rights on economic growth and accurate ways to ascertain the level of democracy (see, for example, Barro 1996Barro , 1998Clague et al 1996;Haan and Siermann 1995;Helliwell 1994;Przeworski and Limongi 1993;Alesina and Perotti 1996;and Londregan and Poole 1996). Although we should expect a positive relationship, the relationship between measures of democracy and economic growth or reforms is much more complex, so conclusive results may not be possible.…”
Section: Variables Data and Econometric Modelmentioning
confidence: 99%